The Development Of Internal Supervision Model For Teacher Competency Development In Secondary Level Mathematics Learning Management For Charitable Schools Of Buddhist Temples (Journal of Namibian Studies : History Politics Culture, 2023)
This research aims to study current conditions and the desirable condition including, construct and examine of internal supervision, to develop teacher competencies in mathematics learning management at the secondary level for charitable schools of Buddhist temples, the experimental and evaluative model of internal supervision was used. This is the Research and Development which is operated in 3 phases as follows:Phase 1) Studied the current and desirable conditions of internal supervision to develop teachers' competencies in mathematics learning management at the secondary level for charity schools of Buddhist temples. The sample group consisted of 7 qualified experts, school administrators and 132 mathematics teachers. Tools used were assessment forms and questionnaires. Phase 2) To create and examine an internal supervision model to develop teachers' competencies in mathematics learning management for Buddhist temples' charitable schools. The sample group consisted of 9 executives who interviewed with Best Practices, a group of expert critics and the draft reviewed experts 5 people and a group of 9 qualified experts for the model confirmation. The tools used were assessment forms. Phase 3) An experiment and evaluation of the internal supervision model to develop teachers' competencies in mathematics learning management for Buddhist temples' charitable schools. The sample group was school administrators and deputy administrators, academic teachers, the core learning subjects heads, 3 mathematics teachers and 120 students. The tools used were tests, assessments, and questionnaires. The statistic in data analysis is the mean and standard deviation. The results showed that:1.The current state of internal supervision for teacher competencydevelopment in mathematics learning management at the secondary level for charity schools of Buddhist temples was at a high level, and the desirable state overall practice was at the highest level, the study of components and indicators consisted of 5 components and 58 indicators.2.The constructing and examining the model that passed the supervision model quality evaluated from the qualified experts have 5 components as Component 1. The principle of the model. Component 2. The purpose of the model. Component 3. Internal supervision process (PIDE2R model) which consists of 5 steps are: 1) Planning: P. 2) Providing knowledge before supervision (Informing: I). 3) Supervision Operations (Doing: D) with 4 sub-steps as: Pre-teaching observation meeting (Pre-Observation conference), Classroom Observation, analyzing data from teaching observation (Analyzing and Data collecting), Meeting after teaching observation (Post-Observation conference). 4) Supervision evaluation (Evaluating: E). 5) Reflecting & Reinforcing: 2R. Component 4. Model Evaluation, and component 5. Conditions for Successful Implementation of the Model.• The results of the trial and evaluation of the internal supervision model for teacher competency development in secondary mathematics learning management for charity schools of Buddhist temples were found that: 1) Knowledge test results and understanding of supervised teachers in mathematics learning management, supervised teachers have higher knowledge than before supervising. 2) The results of supervising teachers' ability to design learning management plans after being supervised have higher learning management abilities than before supervision and assessment results possibility and the usefulness of the supervision model overall, it was at the highest level.